Investigation of energy efficient protocols based on stable clustering for enhancing lifetime in heterogeneous WSNs - Noor Alhuda F. Abbas; Jaber H. Majeed; Waleed Khalid Al-Azzawi; Adnan Hussein Ali (Institute of Advanced Engineering and Science, 2021)
There are certain challenges faced with wireless sensor networks (WSNs) performances, consumption can be seen amongst all these challenges as a serious area of research. Data from sensor nodes are transmitted by most WSN energy either among many nodes or to the base station (BS), and due this connection, several routing protocols were developed for supporting in data transmission in the WSNs. Extending network lifetime in an operational environment is the major objective of the wireless sensor network. Charging or exchanging sensor node batteries is almost impossible. Energy balancing and energy efficiency are significant research scopes as per designing of routing protocols aimed at self-organized WSNs. A heterogeneous WSN is one where every node has different amount of energy linked to it before it is deployed in a network. Therefore, different energy efficient routing protocols have been proposed which enables lesser consumption of energy, longer stability period which leads to the network lifetime increasing. In this study, the average energy of a WSN is computed after every logical round of operation for our protocol-HPEEA and compare it with two well-known heterogeneous protocols namely-SEP and CCS. At the end of the considered number of logical operations, MATLAB with simulation results confirm that HPEEA protocol have a reduction in the energy consumption compared to other protocols.